IMPROVED REFERENCE IMAGE ENCRYPTION METHODS BASED ON 2K CORRECTION IN THE INTEGER WAVELET DOMAIN - Tuncer, Turker; Dogan, Sengul; Tadeusiewicz, Ryszard; Plawiak, Pawel (Univ Zielona Gora Press, 2019)
Many visually meaningful image encryption (VMIE) methods have been proposed in the literature using reference encryption. However, the most important problems of these methods are low visual quality and blindness. Owing to the low visual quality, the pre-encrypted image can be analyzed simply from the reference image and, in order to decrypt nonblind methods, users should use original reference images. In this paper, two novel reference image encryption methods based on the integer DWT (discrete wavelet transform) using 2(k) correction are proposed. These methods are blind and have high visual quality, as well as short execution times. The main aim of the proposed methods is to solve the problem of the three VMIE methods existing in the literature. The proposed methods mainly consist of the integer DWT, pre-encrypted image embedding by kLSBs (k least significant bits) and 2(k) correction. In the decryption phase, the integer DWT and pre-encrypted image extraction with the mod operator are used. Peak signal-to-noise ratio (PSNR) measures the performances of the proposed methods. Experimental results clearly illustrate that the proposed methods improve the visual quality of the reference image encryption methods. Overall, 2(k) correction and kLSBs provide high visual quality and blindness.
Keywords: visually meaningful image encryption; 2(k) correction; discrete wavelet transform; least significant bits embedding